"Reason to Hope?": The White Savior Myth and Progress in "Post-Racial" America. (December 2017) - Maurantonio, Nicole
On April 4, 2015, White North Charleston, South Carolina, Police Officer Michael Slager shot and killed Black motorist Walter Scott. Upon the release of a bystander video of the deadly shooting, Mayor Keith Summey and Police Chief Eddie Driggers denounced Slager's actions and announced his arrest for Scott's death. This article argues that journalists' use and subsequent circulation of White savior mythology to narrativize the work of the two leaders offered a message of hope, progress, and White redemption, anchored in a vision of a "post-racial" United States.